Directory for the Towns of St. John's, Harbor Grace, and Carbonear, Newfoundland, for 1885-86 - Sharpe, John, fl. 1885 (St. John's (N.L.), 1885)
A directory for St. John's, Harbor Grace and Carbonear, 1885-86. Listings are alphabetical with occupation. It includes general social, economic and governmental information about Newfoundland, as well as historical and business information. Includes advertisements.